Comprehensive analysis of transcriptomics and metabolomics to understand tail-suspension-induced myocardial injury in rat - Liu, Yu; Guo, Liguo; Xu, Chong; Liu, Junlian; Fan, Quanchun; Gai, Yuqing; Zhao, Shuang; Wu, Xiaorui; Mi, Tao; Wang, Jiaping; Li, Yongzhi (Frontiers in Cardiovascular Medicine, 2023)
Background/Aims The effect and underlying mechanism of microgravity on myocardium still poorly understood. The present study aims to reveal the effect and underlying mechanism of tail-suspension-induced microgravity on myocardium of rats. Methods Tail-suspension was conducted to simulate microgravity in rats. Echocardiography assay was used to detect cardiac function. The cardiac weight index was measured. Hematoxylin and eosin (HE) staining and transmission electron microscopy assay were conducted to observe the structure of the tissues. RNA sequencing and non-targeted metabolomics was employed to obtain transcriptome and metabolic signatures of heart from tail-suspension-induced microgravity and control rats. Results Microgravity induced myocardial atrophy and decreased cardiac function in rats. Structure and ultrastructure changes were observed in myocardium of rats stimulated with microgravity. RNA sequencing for protein coding genes was performed and identified a total of 605 genes were differentially expressed in myocardium of rats with tail suspension, with 250 upregulated and 355 downregulated (P < 0.05 and | log2fold change| > 1). A total of 55 differentially expressed metabolites were identified between the two groups (VIP > 1 and P < 0.05) by the metabolic profiles of heart tissues from microgravity groups and control. Several major pathways altered aberrantly at both transcriptional and metabolic levels, including FoxO signaling pathway, Amyotrophic lateral sclerosis, Histidine metabolism, Arginine and proline metabolism. Conclusion Microgravity can induce myocardial atrophy and decreases cardiac function in rats and the molecular alterations at the metabolic and transcriptomic levels was observed, which indicated major altered pathways in rats with tail suspension. The differentially expressed genes and metabolites-involved in the pathways maybe potential biomarkers for microgravity-induced myocardial atrophy.